Treatment-related Focal Nodular Hyperplasia Mimicking Liver Metastases. Issue 2 (March 2019) - Laino, Maria Elena; Monti, Serena; Klimstra, David S.; Tang, Laura H.; Mannelli, Lorenzo
Abstract : A 7-year-old patient with a stage 4 neuroblastoma underwent chemotherapy, surgery, myeloablative therapy, external beam radiotherapy, and Isoretinoin treatment. A posttreatment magnetic resonance examination performed administering gadoteric acid as contrast agent showed 2 new hypervascular hepatic lesions, suspicious for metastases. A second magnetic resonance imaging performed using a liver-specific contrast medium (gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid) demonstrated that these lesions were consistent with treatment-related focal nodular hyperplasia.